2015
DOI: 10.1007/s00774-015-0665-3
|View full text |Cite
|
Sign up to set email alerts
|

The importance of assessing the rate of bone turnover and the balance between bone formation and bone resorption during daily teriparatide administration for osteoporosis: a pilot study

Abstract: This study aimed to examine the importance of simultaneously measuring bone formation and resorption markers during daily teriparatide administration. In 135 women with osteoporosis, bone mineral density (BMD) was measured at 0, 24, and 48 weeks after teriparatide administration. Bone-specific alkaline phosphatase and tartrate-resistant acid phosphatase 5b were measured at 0, 4, 12, 24, 36, and 48 weeks. Subanalyses were performed in groups divided according to the BMD change at 48 weeks (increased and decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Bone resorption markers are useful for evaluating bone resorption inhibitors, such as BPs and SERMs, whereas bone formation markers are useful for evaluating bone formation promoters such as teriparatide [11] . However, it is insufficient to evaluate either the bone formation marker or bone resorption marker, when there is any dissociation between observed trends in both markers, such as that occurring in this study [12] . When the effect of denosumab was evaluated only in BAP at week 4, the balance might be underestimated, and when it was evaluated only in TRACP-5b, the turnover rate might be overestimated.…”
Section: Discussionmentioning
confidence: 85%
“…Bone resorption markers are useful for evaluating bone resorption inhibitors, such as BPs and SERMs, whereas bone formation markers are useful for evaluating bone formation promoters such as teriparatide [11] . However, it is insufficient to evaluate either the bone formation marker or bone resorption marker, when there is any dissociation between observed trends in both markers, such as that occurring in this study [12] . When the effect of denosumab was evaluated only in BAP at week 4, the balance might be underestimated, and when it was evaluated only in TRACP-5b, the turnover rate might be overestimated.…”
Section: Discussionmentioning
confidence: 85%
“…Both the bone formation and bone resorption levels might be enhanced in the elderly postmenopausal women in our study, as suggested by the fact that the bone resorption biomarker, β-CTX, was positively correlated with the ALP, OST and P1NP levels in the current study. It has been widely accepted that the net bone gain or loss of the skeleton is determined by the balance of the formation and resorption of the bone (Shieh et al, 2016, Nakatoh, 2016). However, the biomarkers of resorption and formation alone have poor predictive ability for the BMD, since both the bone resorption and formation were increased in subjects with increased bone turnover, regardless of whether there is a net gain or loss of bone.…”
Section: Discussionmentioning
confidence: 99%
“…This standardization method represents the balance of bone formation and resorption, together with the rate of bone turnover, although it does not necessarily reflect the bone remodeling unit and is not a direct assessment at the tissue level. The utility of this standardization method to indicate the overall balance between bone resorption and formation has been previously shown in adults [33][34][35][36], although there is no evidence about their use in children and adolescents.…”
Section: Blood Analysismentioning
confidence: 99%